Reduced susceptibility to fluroquinolone and molecular analysis of ciprofloxacine resistance in salmonella typhi in Bangladesh - Sarker, ABM Sarwer-E-Alom; Saha, Samir K; Islam, Maksuda; Hossain, MA (Dhaka University Journal of Biological Sciences, 2011)
The study of the trend of infection, susceptibility to antibiotics and molecular level analysis of the cause of reduced susceptibility of Salmonella typhi isolates from the patients in Bangladesh were studied. Out of 9040 blood cultures obtained during the study period, 1266 (14.0%) showed significant growth. Nearly three?fourths of the positive blood cultures were due to S. typhi and rests were mostly of S. paratyphi A. The prevalence was highest between the age group 25 and 60 months. Male showed slightly higher rate of infection than female. Among all 943 S. typhi isolates, 42.6, 42 and 41.4% were sensitive to ampicillin, cotrimoxazol and chloramphenicol, respectively. All isolates were sensitive to ceftriaxon and ceftazidim; 9 isolates were ciprofloxacin resistant, others were moderate to highly sensitive; whereas, only 2.2% isolates were sensitive and almost all (97.8%) were found resistant to nalidixic acid. The E?strip test among 411 isolates showed the MIC value of 53 isolates nearer to the very sensitive (< 0.125 μg/ml), 252 isolates between 0.125 and 0.5 μg/ml, 95 isolates between 0.5 and 2.0 μg/ml and rest other 11 isolates showed from > 2.0 μg/ml to very highly resistant (512 μg/ml). VNTR pattern of all ciprofloxacine resistant S. typhi was also same. Restriction fragment analysis of gyrase?A gene indicated point mutations in different loci that bear the cause of being resistant to ciprofloxacin. Key words: Reduced susceptibility; Typhoid fever; Salmonella typhi; Fluoroquinolone DOI: http://dx.doi.org/10.3329/dujbs.v19i2.8955 DUJBS 2010; 19(2): 137-144